CNC milling of face gears with a novel geometric analysis. (September 2019) - Zhou, Yuansheng; Wang, Shenghui; Wang, Liming; Tang, Jinyuan; Chen, Zezhong C.
Highlights: Face gears are cut in popular CNC milling machine tools. The envelope of developable ruled surface is obtained explicitly. An advanced geometry study is proposed to the tool path planning. Tool paths are generated with the biggest allowable cutters. Abstract: Face gears can take advantages in different mechanisms, but the current manufacturing technology is inferior to satisfy the growing industry. CNC (computer numerical control) milling is a popular manufacturing way that could promote the applications of face gears. Generally, CNC milling can be implemented to a product with given CAD (computer-aided design) model by planning the tool paths in commercial CNC machining software. Unfortunately, there is no commercial software available to directly generate their CAD models with given design parameters. Hence, we propose a novel geometric analysis to bridge the gap between the CAD and CNC milling of face gears. First, a novel envelope approach, which calculates the envelope surface of the developable ruled surface as closed-form (explicit) result, is introduced to study the tooth surface geometry of face gears. It obtains the representation of face gear tooth surface as closed-form rather implicit one. Second, the 3D modeling and curvature analysis are implemented as the preparation of tool path planning. Third, a comprehensive algorithm is proposed to generate tool paths by choosing biggest allowable cutters without interference. The algorithm is verified by both simulation and experiment. The results show the validity of the proposed method.